CCR8 marks highly suppressive Treg cells within tumours but is dispensable for their accumulation and suppressive function. Issue 4 (9th May 2021) - Whiteside, Sarah K.; Grant, Francis M.; Gyori, David S.; Conti, Alberto G.; Imianowski, Charlotte J.; Kuo, Paula; Nasrallah, Rabab; Sadiyah, Firas; Lira, Sergio A.; Tacke, Frank; Eil, Robert L.; Burton, Oliver T.; et al.
Abstract: CD4 + regulatory T (Treg) cells, dependent upon the transcription factor Foxp3, contribute to tumour immunosuppression but are also required for immune homeostasis. There is interest in developing therapies that selectively target the immunosuppressive function of Treg cells within tumours without disrupting their systemic anti‐inflammatory function. High levels of expression of chemokine (C‐C motif) receptor 8 (CCR8) discriminate Treg cells within tumours from those found in systemic lymphoid tissues. It has recently been proposed that disruption of CCR8 function using blocking anti‐CCR8 antibodies results in reduced accumulation of Treg cells within tumours and disruption of their immunosuppressive function. Here, using Ccr8 −/− mice, we show that CCR8 function is not required for Treg cell accumulation or immunosuppression in the context of syngeneic MC38 colorectal adenocarcinoma and B16 melanoma tumours. We observed high levels of CCR8 expression on tumour‐infiltrating Treg cells which were abolished in Ccr8 −/− mice. High levels of CCR8 marked cells with high levels of suppressive function. However, whereas systemic ablation of Treg cells resulted in strikingly diminished tumour burden, growth of subcutaneously implanted tumours was unaffected by systemic CCR8 loss. Consistently, we observed minimal impact of systemic CCR8 ablation on the frequency, phenotype and function of tumour‐infiltrating Treg cells and conventional T (Tconv) function. These findings suggest that CCR8 is not required for Treg cell accumulation and immunosuppressive function within tumours and that depletion of CCR8 + Treg cells rather than blockade of CCR8 function is a more promising avenue for selective immunotherapy. Abstract : There is interest in developing therapies that selectively target the immunosuppressive function of Treg cells within tumours without disrupting their systemic anti‐inflammatory function. It has recently been proposed that disruption of CCR8 function using blocking anti‐CCR8 antibodies results in reduced accumulation of Treg cells within tumours and disruption of their immunosuppressive function.​We show that CCR8 marks highly suppressive Treg cells within tumours but is not required for Treg cell accumulation and immunosuppressive function within tumours, suggesting that depletion of CCR8 + Treg cells rather than blockade of CCR8 function is a more promising avenue for selective immunotherapy.